Syed Nawab Haider Naqvi, Mahmood Hasan Khan and M. Ghaffu Otaudhry (edt.). LaJld Reforms in Pakistan, A Historical Perspective. Islamabad: Pakistan Institute of Development Economics 1987. viii+216 pp.Price: Rs 220 (USS 35) for hardcover; Rs 140.00 (USS 20) for soft-cover. (The Pakistan Development Review, 1988)
The authors describe how Pakistan has grappled with land reform, surely one of the most intractable and divisive issues facing agriculture anywhere. The land-tenure system at independence in 1947 included a high degree of land ownership concentration, absentee landlordism, insecurity of tenant tenure, and excessive rent. Land reform since 1947 focused on imposition of ceilings on landholding, distribution of land to landless tenants and small owners, and readjustments of contracts to improve the position of the tenant. These reformist measures have removed some but by no means all of the undesirable characteristics of the system. The authors list as well as present a critique of the reports of five official committees and commissions on land reform. The reports highlight the conflicts and ideologies of the reformers. The predominant ideal of the land reformers is a system of peasant proprietorship although some reformers favoured other systems such as communal farming and state ownership of land, and still others favoured cash rents over share rents. More pragmatic reformers recognized that tenancy is likely to be with Pakistan for the foreseeable future and that the batai (sharecropping) arrangement is the most workable system. According to the editors, the batai system can work to the advantage of landlord and tenant if the ceilings on landholding can be sufficiently lowered (and enforced), the security of the tenant is ensured, and the tenant has recourse to the courts for adjudication of disputes with landlords. Many policy-makers in Pakistan have come to accept that position but intervention by the State to realize the ideal has been slow. The editors conclude that" ... the end result of these land reforms is that they have not succeeded in significantly changing the status quo in rural Pakistan" (p. 29).